Sorption and Preconcentration of Lead on Silica Nanoparticles Modified with Resacetophenone. Issue 3 (2009) - Kaur, Anupreet; Gupta, Usha
Abstract : The silica-resacetophenone (SiO2 -RATP) nanoparticles were used as a new sorbent for extraction of trace amounts of Pb(II) by batch technique. Conditions of the analysis such as preconcentration factor, effect of pH, sample volume, shaking time, elution conditions and effects of interfering ions for the recovery of analyte were investigated. The adsorption capacity of nanometer SiO2 -RATP was found to be 167.24 µ mol/g at optimum pH and the detection limit (3σ) was 0.58 µg/L. The adsorption equilibrium of Pb(II) on nanometer SiO2 -RATP was achieved in 20 min. Adsorbed Pb(II) was easily eluted with 5 mL of 0.5 M hydrochloric acid. The maximum preconcentration factor was 60. The method was applied for the determination of trace amounts of Pb(II) in various natural water rivers.